Deep Electron Density Depletion Near Sunset Terminator on St. Patrick's Day Storm and Its Impacts on Skywave Propagation - M. Ankita; S. Tulasi Ram; K. K. Ajith; S. Sripathi (Space Weather)
Abstract The plasma density distribution in the equatorial and low latitude ionosphere can often be severely disturbed during active space weather events that can have paramount impacts on the long‐distance high frequency (HF) radio wave (Skywave) communications through the ionosphere. On the St. Patrick's Day storm of 17 March 2015, a deep depletion of plasma with more than two orders of magnitude was observed over a narrow longitudinal sector near the sunset terminator. The controlled SAMI2 (Sami2 is Another Model of the Ionosphere) simulations indicate that a large equatorial vertical drift around sunset terminator can produce such a deep electron density depletion and strong reinforcement of equatorial ionization anomaly. The impacts of these ionospheric density disturbances on the Skywave communication systems have been investigated using an HF propagation simulator that solves the propagation path of radio waves under given background ionospheric conditions. The results clearly demonstrate that the usable HF spectrum for Skywave communications is reduced by more than 50% over the region of depletion. Further, large areas of skip zones, where the Skywave signals are not receivable, are produced due to low ionospheric densities over this region. This study can have important applications in the planning and operation of Skywave systems during the active space weather periods.